Wireless Power Transmission. (October 2019) - Bhavya Keerthi, V.; Swetha, V.; Annadevi, E.
Abstract: In recent days, Wireless Power Transfer (WPT) and harvesting energy received lots of attentions due to the necessity of having a flexible, suitable and secure source of energy. With the explosion of wireless technologies including wireless sensor network (WSN) like internet of things, such intelligent systems had highlighted this need. Wireless power transfer is a key technology to enable any device operation without replacing their batteries, often challenging due to cost of replacement and the difficulty to reach inaccessible areas. Anyhow wireless power transfer is being considered as eco-friendly. This also removes the need to dispose dead batteries. Inductive coupling can be used to charge the low power devices quickly and effectively without the help of wires. This method is done by using charging a resonant coil from AC and then transmitting subsequent power to the resistive load. In this case, oscillating circuit is used in the conversion of DC to AC in order to transmit the magnetic field by passing frequency and inducing the receiver coil. The system is designed and constructed as two parts. They are Transmitter part and Receiver part. To calculate the inductive coupling between the transmitter oil and receiver coil, Ampere's Law, Biot-Savart's Law and Faraday's Law are used as per the requirement.